2021
DOI: 10.24006/jilt.2021.19.1.033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trade Liberalization on Asymmetric Countries for Homogenous and Differentiate Product: Case of Pakistan-China Free Trade Agreement

Abstract: The study performs an empirical test to assess the impact of the Pakistan-China Free trade agreement (FTA) on Pakistan, China, and the World's exports under homogenous and differentiated products. This study employs the modeling with Poisson specification with Poisson Pseudo-Maximum Likelihood method for the estimations. The results of empirical test show that the effect of FTA on the FTA and Non-FTA countries is greater in the differentiated product as compared to the homogenous product. Therefore, one of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Two approaches commonly used to examine the impact of FTAs are gravity models (Abidin et al, 2013;Ahmed et al, 2021;Alam, 2015;Ali et al, 2020;Anderson & Yotov, 2016;Dianniar, 2013;Didia et al, 2015;Guan & Sheong, 2020;Hayakawa et al, 2016;Herath, 2014;Lopez, 2019;Mahabir et al, 2020;Urata & Okabe, 2007) and computable general equilibrium (CGE) models (Kartini & Margaret, 2020;Kustiari & Hermanto, 2017;Muchopa et al, 2020;Nekhay et al, 2020;Phat & Hanh, 2019;Rosyadi & Widodo, 2018;Tsutsumi et al, 2019). Bekkers & Rojas-Ramagosa (2018) compared these two models and found that they have distinct advantages while showing a certain degree of convergence in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…Two approaches commonly used to examine the impact of FTAs are gravity models (Abidin et al, 2013;Ahmed et al, 2021;Alam, 2015;Ali et al, 2020;Anderson & Yotov, 2016;Dianniar, 2013;Didia et al, 2015;Guan & Sheong, 2020;Hayakawa et al, 2016;Herath, 2014;Lopez, 2019;Mahabir et al, 2020;Urata & Okabe, 2007) and computable general equilibrium (CGE) models (Kartini & Margaret, 2020;Kustiari & Hermanto, 2017;Muchopa et al, 2020;Nekhay et al, 2020;Phat & Hanh, 2019;Rosyadi & Widodo, 2018;Tsutsumi et al, 2019). Bekkers & Rojas-Ramagosa (2018) compared these two models and found that they have distinct advantages while showing a certain degree of convergence in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies suggest that Pakistan–China FTA is equally beneficial for both Pakistan and China (Kataria and Naveed, 2014; Farrukh et al ., 2013; Junaid and Manzoor, 2017; Kataria and Naveed, 2014; Irshad et al ., 2016; Liu, 2010; Kabraji, 2012; Ahmed et al. , 2021a, b). According to Kataria and Naveed (2014), Pakistan is the first country located in South Asia that have a free trade agreement with China.…”
Section: Literature Reviewmentioning
confidence: 99%